The relationship between sleep disorders in the last month of pregnancy and the length of labor and mode of delivery in pregnant women referring to Abadan Taleghani Hospital in 2017 - Zeinab Raiesifar; Salar Kamangar; Noorollah Tahery; Shahram Baraz; Seyed Ziaoodin Moosavi; Pouriya Darabiyan; Parvin Ghezebash; Afsaneh Raiesifar (Mashhad University of Medical Sciences, 2019)
Introduction: Sleep disorders in addition to physical and psychological consequences for pregnant women may affect their labor duration and mode of delivery. This study was performed with aim to determine the relationship between sleep disorders in the last month of pregnancy with labor duration and mode of delivery. Methods: This descriptive study was performed on 147 pregnant women referred to the maternity of Abadan Ayatollah Taleghani Hospital in 2017. Data collecting tools included two section of demographic and pregnancy information, and Pittsburgh sleep quality (PSQI). The variables of this study were labor length, mode of delivery and quality of sleep. Data were collected during 3 months. Data were analyzed using SPSS software (version 18) and Chi-square, Independent T-test and ANOVA tests. P<0.05 was considered statistically significant. Results: The mean score of sleep quality in pregnant women was 8.86 ± 4.2 and mean length of labor was 3.53±2.1 h. Also, 74 women (50.3%) had vaginal delivery and 73 (49.7%) had cesarean delivery. Moreover, 47 (64.5%) of women with cesarean section had sleep disorder, while sleep disorders were observed only in 35.5% (26) of women with vaginal delivery. Mean duration of labor in women who have had sleep disorder was significantly higher than those without sleep disorder (p= 0.04). Also, vaginal delivery was significantly higher in women without sleep disorder (p <0.0001). Conclusion: There was statistically significant relationship between sleep disorders in pregnancy and duration of labor, also the prevalence of cesarean delivery was higher in women with sleep disorders.